Almost an outlaw - Burnham, Molly B. (Burnham, Molly B. Teddy Mars, 2017)
When his strict great-aunt promotes rules that threaten the neighborhood pigeons, Teddy may have to bend a few rules to save themeven if it means to team up with his pesky little brother, also known as The Destructor.